Simulation of signalized intersection functioning with fuzzy control algorithm - Zinoviy STOTSKO; Yevhen FORNALCHYK; Ihor MOHYLA (Transport Problems, 2013)
In the course of research the fuzzy algorithm for traffic control at signalized intersection has been developed. Based on the results of simulating of intersection functioning during an hour and a day it has been established that using of developed fuzzy algorithm enables to reduce average and maximal queue lengths of vehicles before the intersection owing to adaptation of control system parameters to traffic flow volumes.